ความสัมพันธ์ระหว่างปัจจัยส่วนบุคคล ค่านิยมทางสุขภาพ และสภาพแวดล้อมในสถาบันกับพฤติกรรมส่งเสริมสุขภาพของนักศึกษาพยาบาล สถาบันการศึกษาพยาบาลเขตกรุงเทพมหานคร - ปาริชาติ สุขสวัสดิพร (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purposes of this study were to examine the relationships between personal factors, health values, institutional environment and health promoting behaviors of nursing students in educational nursing institution in Bangkok Metropolis and to explore the variables that predicted health promoting behaviors of nursing students. Subject were 394 nursing students who studying in bachelor degree of nursing science in class 2, 3 and 4, educational nursing institution in Bangkok Metropolis. Data were collected by using 4 sets of questionnaires: demographic data form, health values, institutional environment and health promotion behaviors of nursing students. The questionnaires were tested for content validity and the reliability by cronbach s alpha coefficient were .83, .88 and .80. Data were analyzed by percentage, mean, standard deviation, chi-square, pearson product moment correlation and stepwise multiple regression analysis the significant at the .05 level. The major findings were as follows: 1. Health promoting behaviors of nursing students in educational nursing institution, Bangkok Metropolis was at the high level 2. Health values and institutional environment of nursing students were at the high level. 3. Personal factor, in term of origin was significantly correlated with health promoting behaviors of nursing students but class and income were not significantly correlated with health promoting behaviors of nursing students at the .05 level. 4. Health values and institutional environment were positive significantly correlated with health promoting behaviors of nursing students at the .05 level. 5. Factors that significantly predicted health promoting behaviors of nursing students in stepwise multiple regression analysis at the .05 level were 7 predictor variables and able to account for 48.1 percent (R2 = .481) of the variance. The variables were: (1) health values of nutrition (2) health values of spiritual development (3) psychological environment in practice nursing institution (4) Northeastern origin (5)health values of cleaning (6) health values of using product and health service and (7) Eastern origin. The predicted equation in standard score form can be stated as follows: Health promoting behaviors of nursing students = .299 (health values of nutrition) + .188 (health values of spiritual development) + .196 (psychological environment in practice nursing institution) + .176 (Northeastern origin) + .175 (health values of cleaning) + .122 (health values of nursing product and health service) + .080 (Eastern origin)